Making sense of fatherhood : gender, caring and work - Miller, Tina, 1957- (Cambridge : Cambridge University Press, 2011)
As family and work demands become more complex, who is left holding the baby? Tina Miller explores men's experiences of fatherhood and provides unique insights into paternal caring, changing masculinities and men's relations to paid work. She focuses on the narratives of a group of men as they first anticipate and then experience fatherhood for the first time. Her original, longitudinal research contributes to contemporary theories of gender against a backdrop of societal and policy change. The men's journeys into fatherhood are both similar and varied, and they illuminate just how deeply gender permeates individual lives, everyday practices and societal assumptions around caring for young children. This book acts as a companion to Making Sense of Motherhood (Cambridge University Press, 2005) and, together, these innovative studies reveal how gendered practices around caring become enacted.
Machine generated contents note: Introduction; 1. Gendered lives and caring responsibilities: an overview; 2. Gendered discourses: men, masculinities and fatherhood; 3. Anticipating fatherhood: 'being there'; 4. Making sense of early fathering experiences; 5. A return to a new normal: juggling fathering and work; 6. Gendering practices: motherhood and fatherhood expectations and experiences; 7. Conclusions and reflections.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Fatherhood